POPULATION DYNAMICS OF THE NEMATODE PRATYLENCHUSBRACHYURUS IN DIFFERENT PRODUCTION SYSTEMS IN MT - E. Ferrari; E. U. Ramos Junior; G. Tavares; V. O. Faleiro; H. F. Shiomi; H. Debiasi; J. C. Franchini (Scientific Electronic Archives, 2016)
This study aimed to evaluate the influence of different cultures second crop on the population of the nematode P. brachyurus, and the soybean crop productivity. The experiment was conducted at Embrapaagrosilvopastoral during agricultural year 2012/13, 2013/2014 and 2014/15, 0.4 ha of tracks. During the 2012/2013 crop soybeans planted in every area, in the off-season in 2013, two corn cultivars, two soybean and corn consortium with B. ruziziensis in 2013/14 crop was sown soybeans again in the off-season 2014 They were sown three soybean cultivars, a cultivar of corn and intercropping of millet with C. ochroleuca. In the season 2014/15 soybean was sown in every area and in the off-season 2 cultivars of maize and 3 soybean cultivars. Productivity was determined and the population of the P. brachyurus in roots. It was observed that millet consortium and C. ochroleuca were efficient in controlling the nematode. There were differences of reactions not only among species but within species and between the genotypes and soybeans, interfering with the population of the P. brachyurus. In the season 2013/2014 the soybean yield was influenced by the treatments, but the harvest 2014/2015 there was no statistical difference.